Faces in the Stone: Further Finds of Anthropomorphic Engravings Suggest a Discrete Artistic Tradition Flourished in Timor-Leste in the Terminal Pleistocene. Issue 1 (February 2021) - O'Connor, Sue; Oliveira, Nuno Vasco; Standish, Christopher D.; García-Diez, Marcos; Kealy, Shimona; Shipton, Ceri
Abstract : Engraving sites are rare in mainland and Island Southeast Asia (ISEA) where painted art dominates the prehistoric artistic record. Here we report two new engraving sites from the Tutuala region of Timor-Leste comprising mostly humanoid forms carved into speleothem columns in rock-shelters. Engraved face motifs have previously been reported from Lene Hara Cave in this same region, and one was dated to the Pleistocene–Holocene transition using the Uranium–Thorium method. We discuss the engravings in relation to changes in technology and material culture that took place in the terminal Pleistocene and early Holocene archaeological records in this region of Timor as well as neighbouring islands. We suggest that the engravings may have been produced as markers of territorial and social identity within the context of population expansion and greater inter-group contacts at this time.